e = 2 e = 3 e = 4 e = 5 e = 6 e = 7 e = 8
m = 2 (m,n) = (2,2)
G' = 1
m = 3 (m,n) = (3,3)
G' = (3)
m = 4 (m,n) = (4,4) (m,n) = (4,5)
G' = (3,3) G' = (3,3,3) G' = (3,3,3,3)
         /
m = 5 (m,n) = (5,5) (m,n) = (5,6) (m,n) = (5,7)
G' = (9,3) G' = (9,3,3) G' = (9,3,3,3)
m = 6 (m,n) = (6,6) (m,n) = (6,7) (m,n) = (6,8) (m,n) = (6,9)
G' = (9,9) G' = (9,9,3) G' = (9,9,3,3) G' = (9,9,9,3) G' = (9,9,9,9)
         /
m = 7 (m,n) = (7,7) (m,n) = (7,8) (m,n) = (7,9) (m,n) = (7,10) (m,n) = (7,11)
G' = (27,9) G' = (27,9,3) G' = (27,9,3,3) G' = (27,9,9,3) G' = (27,9,9,9)
m = 8 (m,n) = (8,8) (m,n) = (8,9) (m,n) = (8,10) (m,n) = (8,11) (m,n) = (8,12) (m,n) = (8,13)
G' = (27,27) G' = (27,27,3) G' = (27,27,3,3) G' = (27,27,9,3) G' = (27,27,9,9) G' = (27,27,27,9) G' = (27,27,27,27)
         /
m = 9 (m,n) = (9,9) (m,n) = (9,10) (m,n) = (9,11) (m,n) = (9,12) (m,n) = (9,13) (m,n) = (9,14) (m,n) = (9,15)
G' = (81,27) G' = (81,27,3) G' = (81,27,3,3) G' = (81,27,9,3) G' = (81,27,9,9) G' = (81,27,27,9) G' = (81,27,27,27)